UTILIZATION OF TEA AND USED BOTTLES AS A MEDIUM TO GROW KANGKUNG VEGETABLE HYDROPONICS IN BULAKAMBA VILLAGE - Salsabila, Berliana Berma; Novita, Rizki Dwi; Islamiati, Dian Nur; Apriliani, Dwi Rahmi; Fitriyani, Vina (Universitas Negeri Semarang, 2020)
Abstract Land kale (Ipameareptans Poir) is a short-lived type of vegetable plant with a high nutritional content, namely vitamins A, B, C, protein, calcium, sterol silo, phosphorus, and mineral ingredients in the form of iron that is useful for the growth and health of the body. The need for vegetables in the market is quite high, household land is reduced, and this large amount of plastic bottle waste leads to the need for new innovations in households to grow vegetables independently using a simple hydroponic system. Therefore, this community service aims to provide knowledge and training to the community about the influence of tea amps used as a substitute for simple household hydroponic planting media. The methods used are lecture methods and simulation and practice methods. Tea amps contain several elements such as zinc (Zn), phosphorus (P), nitrogen (N), copper magnesium (Mg), and calcium (Ca) that can help grow crops. Thus, based on observations of kale seeds at the age of Â±2 weeks has reached a height of 12-15cm and is ready to harvest at the age of 3-4 weeks. Kangkung darat (Ipameareptans Poir) merupakan jenis tanaman sayur yang berumur pendek dengan kandungan gizi yang cukup tinggi, yaitu vitamin A, B, C, protein, kalsium, silo sterol, fosfor, dan bahan-bahan mineral berupa zat besi yang berguna bagi pertumbuhan dan kesehatan badan. Kebutuhan akan sayur di pasaran yang cukup tinggi, lahan rumah tangga yang berkurang, serta limbah botol plastik yang banyak ini menyebabkan perlu adanya inovasi baru di rumah tangga untuk menanam sayuran secara mandiri dengan menggunakan sistem hidroponik sederhana. Oleh karena itu, pengabdian masyarakat ini bertujuan untuk memberikan pengetahuan dan pelatihan kepada masyarakat mengenai pengaruh ampas teh yang digunakan sebagai pengganti media tanam hidroponik rumah tangga secara sederhana. Metode yang digunakan adalah metode ceramah dan metode simulasi dan praktek. Ampas teh mengandung beberapa unsur seperti seng (Zn), fosfor (P), nitrogen (N), tembaga magnesium (Mg), dan kalsium (Ca) yang dapat membantu menumbuhkan tanaman. Sehingga, berdasarkan pengamatan benih kangkung pada usia Â±2 minggu telah mencapai tinggi 12-15cm dan siap panen pada usia 3-4 minggu.